Practical Glimpse : learn to edit and create digital photos and art with this powerful open source image editor - Whitt, Phillip (Digital image editor) (Apress, 2020)
Learn how to edit images and create compelling digital art with Glimpse, the newest open source alternative to Adobe Photoshop and GIMP. This book explores Glimpse's broad selection of tools and features that can create beautiful (raster) digital art; painting, drawings, and art created from photos by applying one of the many filters to create artistic effects. You will quickly become acquainted with this powerful program and understand how to use workspace tools and layers. You will learn step-by-step how to correct exposure, digitally retouch and repair damaged photos, and handle just about any photo editing task--even colorizing grayscale images. Practice files are provided with step-by-step instructions to jump into photo editing and art creation. Glimpse is a powerful program that is a viable alternative to Adobe Photoshop and other proprietary software. The possibilities of the art one can create are almost limitless--get started with it using this book today. You will: Navigate the Glimpse workspace Use layers, which are essential in any professional quality image editing program Work with the varied tools that Glimpse offers Enhance, retouch, and modify digital images Restore and repair damaged family photos, and create composites such as replacing backgrounds Create compelling digital artwork using the drawing tools and by applying artistic filters.